The Effect of Carrageenan Concentration on the Physical and Chemical Properties of Gummy Turmeric Acid Jamu - Nurul Rochmawati; Dian Eka Ermawati (Faculty of Pharmacy, Universitas Gadjah Mada, 2021)
Turmric acid Jamu is an Indonesian herbal drink that made from turmeric and tamarind. The herbal medicine industry in Sleman Yogyakarta produces Turmric acid Jamu, but the concentration of curcuminoid has not been determined. Consumers of Turmric acid Jamu are limited to women and adults. Children rarely want to consume jamu, even though the curcuminoid in turmeric can increase appetite, especially for todler. Innovation is needed to process Turmric acid Jamu into products that more desirable and efficacious. Gummy is made with the addition of a gelling agent so that the texture is chewy. Carrageenan is a gelling agent made from seaweed and is safe for food products. The purpose of this study was to determine the effect of variations in carrageenan concentrations on physical and chemical properties, also to determine the optimum concentration of carrageenan in gummy Turmric acid Jamu according to the Indonesian National Standard on soft candy. This research is an experimental laboratory with variations in the concentration of carrageenan (7.5%; 8.0%; 8.5%) and Turmric acid Jamu as the main ingredient. The test include organoleptic, pH, weight uniformity, water content, disintegration time and the respondent acceptance test. The concentration of curcuminoid using spectrophotometry UV-VIS method and statistical analysis. The results showed that carrageenan concentration affected organoleptic, weight uniformity, moisture content, and disintegration time, but did not affect pH. The curcuminoid concentration of Turmric acid Jamu was 1.47% and the gummy was 0.03% (w/w). The carrageenan concentration of 8.0% is the optimum formula because it meets the quality requirements of the gummy and is the most preferred by the respondents.